2006
DOI: 10.1109/tsm.2006.883593
|View full text |Cite
|
Sign up to set email alerts
|

Robust Cu Dual Damascene Interconnects With Porous SiOCH Films Fabricated by Low-Damage Multi-Hard-Mask Etching Technology

Abstract: Low-damage hard-mask (HM) plasma-etching technology for porous SiOCH film ( = 2 6) has been developed for robust 65-nm-node Cu dual damascene interconnects (DDIs). No damage is introduced by fluorocarbon plasma etching irrespective of whether rigid ( = 2 9) or porous ( = 2 6) SiOCH films are used, due to the protective CF-polymer layer deposited on the etched sidewall. The etching selectivity of the SiOCH films to the inorganic HMs is kept high by controlling the radical ratio of carbon relative to oxygen in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In general, to successfully form a dual damascene structure in low-k material, hard masks such as SiO2 or SiN are used to protect the low-k films from the unnecessary chemical reactions with radicals or ions in the plasma process [1][2]. On the other hand, as many papers report, UV light has been used as a cure technique of low-k film for polymerization and porogen burnout [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, to successfully form a dual damascene structure in low-k material, hard masks such as SiO2 or SiN are used to protect the low-k films from the unnecessary chemical reactions with radicals or ions in the plasma process [1][2]. On the other hand, as many papers report, UV light has been used as a cure technique of low-k film for polymerization and porogen burnout [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hard masks such as SiO 2 or SiN are used to protect the low-k films from undesirable chemical reactions with radicals or ions in the plasma process. [5][6][7][8] Figures 1 and 2 show examples of typical process flows of dual-damascene formation with low-k materials. In the processes such as the via-hole/trench reactive ion etching (RIE) process, resist ashing after the etching process, resist ashing in rework and the second hard mask deposition on the first hard mask, the low-k film surface is always covered with a hard mask and never exposed to the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Via‐first DD formation with S‐MAP eliminates the undesirable SiO 2 fence around the top of via holes. Similarly, multi‐layer hard masks with several inorganic films, such as SiO 2 /SiN/SiO 2 , on BARC and photoresist coatings are used to create a stacked low‐k film . The capping layer of SiO 2 reduces plasma‐induced damage and increases resistance in the CMP process.…”
Section: History Of Development Of Multilevel Interconnect Technologymentioning
confidence: 99%
“…For oxygen‐containing plasma treatment, Ohtake et al reported a via‐first multi‐hard‐mask process for the DD structure in porous SiOCH film with no exposure to O 2 ‐ashing plasma. In addition, they reported that nitrogen‐based plasma with oxygen and high‐molecular‐weight fluorocarbon gas (C > 2) chemically modifies the sidewall surface of the etched low‐k film .…”
Section: Process Optimizations and Improvementsmentioning
confidence: 99%
“…To reduce the low-k damage, a multihard mask (MHM) process using thin SiN/SiO SiN has been developed [8]. By the MHM process, the ashing damage is reduced significantly, however, the shouldering of thin HM layers increases the deviation in the line width as well as the line-edge roughness, resulting in the interline shortage especially in scaled-down interconnects.…”
mentioning
confidence: 99%